A place of understanding: Patients' lived experiences of participating in a sexual rehabilitation programme after heart disease - Palm, Pernille; Missel, Malene; Zwisler, Ann‐Dorthe; Svendsen, Jesper Hastrup; Giraldi, Annamaria; Berg, Selina Kikkenborg (Scandinavian Journal of Caring Sciences, 2020)
Abstract Aims and objectives The aim of this project was to explore the lived experience of participating in a nonpharmacological sexual rehabilitation programme. Background In the healthcare system, patients are important stakeholders, and their experience and knowledge are essential to include when evaluating rehabilitation programmes. Patient experiences with participating in sexual rehabilitation for cardiovascular patients have not yet been investigated. Methods Ten qualitative interviews were conducted with male patients from a randomised controlled trial investigating the effect of a 12‐week rehabilitation programme focusing on sexuality. The analysis was inspired by Paul Ricoeur's theory of interpretation. Analysis consisted of three levels: (i) naive reading, (ii) structural analysis and (iii) critical interpretation and discussion. The theoretical framework reflects aspects of behavioural theory of social cognitive theory developed by Albert Bandura and his concept of self‐efficacy. Results The findings are presented as themes extracted from the structural analysis and interpreted in the critical interpretation and express the way in which cardiovascular patients experience participating in a sexual rehabilitation programme. Three themes were identified reflecting the intervention to be a special place of understanding, describing the intervention as a supporting atmosphere and finally expressing the intervention as empowering sexuality. Conclusions Participating in the sexual rehabilitation programme was experienced as efficient, valuable, motivating and safe, but dependent on a professional setting. The intervention developed participants' self‐efficacy with regard to their sexual performance and relationship. Relevance to clinical practice The findings highlight the importance of a professional setting including certain competencies such as humour and professional skills when handling the after‐care of cardiovascular patients with sexual problems.